Evaluation of English Technical Training of Home Affairs Ministry at The Agency of Human Resources Development of Home Affairs Ministry - Chomsyah Putra (CV The Journal Publishing, 2023)
Training evaluation is an effort to determine the effect of Technical Training Material and Key Note Speakers on the Performance of the Technical Training Committee. This Research aims to examine the implementation of technical training in English for home ministry civil servants at the Agency of human resources development of home affairs ministry. Data collection is done through a questionnaire. The questionnaire is used to measure H1= There is an effect of technical training material (X1) on the achievement of the committee (Y). There is an effect of the keynote speaker on the committee (Y). H=3 There are effects of Material (X1) and keynote speaker (X2) simultaneously on the achievement of the committee. Data analysis through multiple regression. Multiple regression analysis aims to determine whether or not there are effects of two or more independent variables (X) on the dependent variable Test (Y). The T-test aims to determine whether or not there is a partial effect given by the independent variable (X) on the dependent variable ( Y). The F-test aims to determine whether or not there is a simultaneous effect given by the independent variable (X) on the dependent variable (Y), and the coefficient of determination serves to determine how much percentage of influence is given by variable x simultaneously on variable y.. The results showed that the Sig. for the effect of X1 on Y is 0.002 <0.05 and the value of t count is 3.201 > t table 2.00247, therefore it can be concluded that H1 is accepted which means there is an effect of X1 on Y.